2022
DOI: 10.3390/nu14061143
|View full text |Cite
|
Sign up to set email alerts
|

Review of Dietary Recommendations for Twin Pregnancy: Does Nutrition Science Keep Up with the Growing Incidence of Multiple Gestations?

Abstract: Recommendations for nutrition and the use of dietary supplements for pregnant women are updated on regular basis but it remains to be seen to what extent they may be applicable in twin pregnancies. The aim of this narrative review is to present the current state of knowledge about the energy and nutrient demand in twin pregnancy. There is general consensus in literature that the energy demand is higher than in a singleton pregnancy, but there is a lack of position statements from scientific societies on specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 99 publications
0
4
1
1
Order By: Relevance
“…Concerning the influence of sociodemographic and reproductive factors on the total IES-2 score, twin pregnancy, pg-BMI, household welfare, and having a current illness were the most influencing factors. Regarding the type of pregnancy, we did not find studies to back up our observation; however, we propose a hypothesis to explain our finding: it has been reported that women with twin pregnancies experience vomiting, nausea, poor appetite, early satiety, and physical discomfort more often than women with singleton pregnancy, due to an enlarged uterus [39,40]. These physical sensations may trigger increased awareness of hunger and satiety cues and thus higher intuitive eating scores.…”
Section: Discussioncontrasting
confidence: 53%
“…Concerning the influence of sociodemographic and reproductive factors on the total IES-2 score, twin pregnancy, pg-BMI, household welfare, and having a current illness were the most influencing factors. Regarding the type of pregnancy, we did not find studies to back up our observation; however, we propose a hypothesis to explain our finding: it has been reported that women with twin pregnancies experience vomiting, nausea, poor appetite, early satiety, and physical discomfort more often than women with singleton pregnancy, due to an enlarged uterus [39,40]. These physical sensations may trigger increased awareness of hunger and satiety cues and thus higher intuitive eating scores.…”
Section: Discussioncontrasting
confidence: 53%
“…One prior study evaluated the extent to which midpregnancy weight gain predisposes an individual to developing GDM in twin pregnancies but did not find a significant effect [ 33 ]. Furthermore, while is it generally agreed that individuals pregnant with twins should increase their energy intake, more precise recommendations considering factors such as GDM, preprengancy BMI, and gestational weight gain are lacking [ 34 , 35 ]. While additional data on gestational weight gain in twin pregnancy is awaited, we recommend a clinical focus on prepregnancy planning with the aim of attaining a healthy BMI before conception.…”
Section: Discussionmentioning
confidence: 99%
“…Передчасні пологи є не тільки медичною, а й соціальною проблемою, яка пов'язана з високими показниками перинатальної захворюваності та смертності передчасно народжених немовлят [7,[11][12][13][14]. Незважаючи на значний прогрес у медичній науці, частота передчасних пологів у світі залишається високою і коливається у межах 8-12 % [15][16][17][18][19].…”
Section: результати дослідження та їх обговоренняunclassified